2008
DOI: 10.1590/s0034-71672008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Violência sexual contra criança no meio intrafamiliar atendidos no SAMVVIS, Teresina, PI

Abstract: ABSTRACT ABSTRACT ABSTRACT This study deals with the characterization of sexual violence in children seen at the Services for the Assistance of Women Victims of Sexual Violence (SAMVVIS) from 2004 to 2007 in Teresina, PI. Data collected from 229 charts indicate that the age of the children varies from less than one year up to 12 years of age. The identification of the aggressor was the neighbor (29.7%), stepfather (11.4%), father (9.4%) and uncle with 8.4%. In regards to the occupation of the aggressor, 20.35%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
23

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 6 publications
0
2
0
23
Order By: Relevance
“…Se somadas as agressões praticadas pelo núcleo familiar (pai, mãe, familiares, padrasto), a proporção é muito maior. Entre adolescentes, predominaram agressores conhecidos fora da família, perfil semelhante ao encontrado por Monteiro et al 15 em Teresina, Piauí. Ainda entre adolescentes, o companheiro apresentou destaque, demonstrando que, com o avanço da idade a violência contra criança ganha contornos de violência doméstica e de gênero.…”
Section: Introductionunclassified
“…Se somadas as agressões praticadas pelo núcleo familiar (pai, mãe, familiares, padrasto), a proporção é muito maior. Entre adolescentes, predominaram agressores conhecidos fora da família, perfil semelhante ao encontrado por Monteiro et al 15 em Teresina, Piauí. Ainda entre adolescentes, o companheiro apresentou destaque, demonstrando que, com o avanço da idade a violência contra criança ganha contornos de violência doméstica e de gênero.…”
Section: Introductionunclassified
“…Observa-se ainda o predomínio da violência entre mulheres negras, na maioria das vezes, aquelas que estão desprovidas da possibilidade de acesso aos serviços de saúde e dos órgãos de denúncia e acompanhamento da violência. Nota-se que, a maioria dos casos notificados está relacionada à baixa renda familiar, de modo que, alguns familiares encaminham essas adolescentes para lares de vizinhos e parentes, na tentativa de minimizar a situação de dificuldade financeira em que vivem, mas os agressores aproveitam o momento de fragilidade individual e social para cometerem suas ações (12) . Entende-se que, a violência perpetrada contra a adolescente acarreta consequências físicas, psíquicas, cognitivas, sociais e emocionais, especialmente quando se torna rotineira (18) .…”
Section: Methodsunclassified
“…When asked about the victims who sought the service, they reported that they were women and children of the female gender, coming from the capital or even from the state's inland. The prevailing age group is 10 to 19 years, although there were cases from children under one year old to the elderly, as described in the literature 15 . Considering Art.…”
Section: Analysis Of Public Health Care Policies For Victims Of Sexuamentioning
confidence: 99%